Strategy and Performance of Foreign Institutional Investors in Chinese Stock Market - Cao, Wenjuan (2007)
QFII (Qualified Foreign Institutional Investor) scheme is a specific policy designed for emerging countries whose currency can not be converted freely and capital market has not been fully opened to foreign investors. It is popular in many emerging markets such as Korea, Taiwan, and India. Experiences in those markets have showed the effectiveness and feasibility to promote their market liberalization in an appropriate and reasonable way. Therefore, China launched its QFII (Qualified Foreign Institutional Investor) scheme on December 1st 2002. The purpose of implementing QFII system in China is to attract foreign institutional investments and educate domestic investors, as well as being a meaningful step to open Chinese stock market. The Chinese stock market has undergone dramatic changes within these years of reform and opening up. As a milestone of Chinese stock market liberalization, the implementation of QFII has a huge impact on the capital market. Its investment strategy and performance, and whether it has achieved expected effect are all of great concern by both Chinese and foreign investors. This paper based on the existing literature on the emerging stock market liberalization, analyses the holding shares of QFIIs in China and their portfolio returns to find out QFIIs investment characteristics and performance and illustrate some investment methods that domestic investors should learn from. It is concluded that QFIIs prefer merit-based shares of traditional periodicity industries, associated with the macro-economy and hard to enter and quit. Although their investment philosophy is worth learning, there is no obvious evidence shows that QFIIs have outstanding performance. From the aspect of long-term, their returns are almost the same as the market average returns, both whole and separated markets.